Phosphorus nanoparticles combined with cubic boron nitride and graphene as stable sodium-ion battery anodes. (1st May 2017) - Ding, Xuli; Huang, Yangyang; Li, Guolong; Tang, Yang; Li, Xiaocheng; Huang, Yunhui
Abstract: Considerable attention has been paid to sodium-ion batteries (SIBs) for large-scale energy storage due to low cost and abundant Na source. Phosphorus (P) is proposed as a high-capacity SIB anode material with theoretical capacity of 2596 mAh g −1 . However, the large volume expansion of P during sodiation brings about a series of challenges, including rapid capacity decay and slow ion transport. In this work, we develop an amorphous P ( α P) anode material with cubic boron nitride (c-BN) as a mechanical skeleton wrapped by nanoporous graphene (pGra) networks, which can combine synergistically the advantages of pGra and c-BN, and hence simultaneously solve the challenges for the P-based anodes. The rigid nature of c-BN is effective to suppress the severe volume expansion during P sodiation process, while the porous network of pGra serves as transport channel for electrons and ions, offering short pathways for large-radii Na + ions diffusion. The α P/c-BN/pGra composite anode shows excellent cyclability with a stable specific capacity of ∼1000 mAh g −1 and ∼90% capacity retention after 100 cycles at a specific current of 50 mA g −1 . The rigid c-BN and flexible pGra provides a promising pathway for developing high performance alloy-based materials for low-cost SIBs.